Clinical Features of NMDAR Ab-mediated Encephalitis - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from University of Oxford, Birmingham Children's Hospital, Guy's and St Thomas', London, UK, performed a prospective surveillance study in children with NMDAR-Ab-mediated neurological disease reported from Nov 2010 to Dec 2011.